Comparison of longitudinal changes in four surrogate insulin resistance indexes for incident T2DM in middle-aged and elderly Chinese - Pan, Liang; Gao, Yu; Han, Jing; Li, Ling; Wang, Miyuan; Peng, Hongye; Liao, Juan; Wan, Hua; Xiang, Guohua; Han, Yangyun (Frontiers in Public Health, 2022)
Abstract Objective: Previous studies suggested a significant relationship between four surrogate indexes and subsequent type 2 diabetes mellitus (T2DM). But the association of longitudinal changes in CVAI, LAP, Tyg, and TG/HDL-C indexes with the risk of T2DM remained uncertain. We aimed to compare the changes in those four insulin resistance surrogate indexes for predicting T2DM in middle-aged and elderly Chinese. Methods: We extracted data from the China Health and Retirement Longitudinal Study (CHARLS). Multivariate logistic regression models were used to estimate odds ratio (OR) with 95% confidence interval (CI) of incident T2DM with for surrogate indexes. The restricted cubic spline analysis was used to examine potential nonlinear correlation and visualize the dose–response relationship between four indexes and T2DM. The receiver operator characteristic curve was used to compare the performance of the four indexes to predict T2DM. Results: We enrolled 4,596 participants in total, including 504 (10.97%) with T2DM. Analysis results showed that four surrogate indexes were associated with T2DM, and the multivariate-adjusted ORs (95% CIs) of T2DM were 1.08 (1.00–1.16), 1.47 (1.32-1.63), 1.12 (1.00–1.25), and 2.45 (2.12–2.83) for each IQR increment in CVAI-D, LAP-D, TG/HDLC-D, and Tyg-D, respectively. Restricted cubic spline regression showed a nonlinear correlation between four surrogate indexes and the risk of T2DM (p for nonlinear < 0.001). From the ROC curve, Tyg-D had the highest AUC, and its AUC values were significantly different from other three indexes both in male and female (all P<0.001). Conclusion: Compared with other indexes, our study found that the longitudinal change in Tyg-D was a better predictor in the clinical setting for identifying individuals with T2DM in middle-aged and elderly Chinese. Monitoring long-term changes in Tyg might help in the early identification of individuals at high risk of T2DM.